1994
DOI: 10.1007/bf00932688
|View full text |Cite
|
Sign up to set email alerts
|

Die Wirkung des Anthelminthikums Levamisol auf ersteAngiostrongylus cantonensis-Larven in infizierten Ratten

Abstract: Effects of levamisole, orally administered at 1, 3, 5 or 7 successive daily doses of 30 mg/kg, on the number of first-stage larvae of Angiostrongylus cantonensis released in the faeces of treated rats were examined. First-stage larval counts (larvae per gram of faeces per female worm recovered, LPG/female) were conspicuously reduced 1 day after administration in all treated groups. In the group treated with a single dose, the larval counts increased 2 days after administration, but no larvae could be detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Experimental animal studies have shown levamisole to significantly reduce worm/larval burden, with the earliest administration (1–5 days post-infection) showing the most efficacy [ 37 , 38 , 39 , 40 , 41 ]. However, due to side effects such as agranulocytosis and its use as a cocaine adulterant, levamisole has been withdrawn from many global markets and is no longer available in many countries, including the US [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental animal studies have shown levamisole to significantly reduce worm/larval burden, with the earliest administration (1–5 days post-infection) showing the most efficacy [ 37 , 38 , 39 , 40 , 41 ]. However, due to side effects such as agranulocytosis and its use as a cocaine adulterant, levamisole has been withdrawn from many global markets and is no longer available in many countries, including the US [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%